Sleep disorders and their relation to injuries among young elite soccer players - M. S. Butovskiy; G. I. Malyakin; E. S. Kapralova; T. M. Vakhidov; E. D. Koroleva (National Electronic Information Consortium (NEICON), 2023)
Aim: to study the quality of sleep and the relationship between sleep disorders and injury among young elite soccer players.Methods: the study summarizes data from relevant questionnaires obtained through anonymous cohort testing of 236 male football players from leading football academies, two farm teams of leading Russian Premier League clubs and three national youth teams.Results: the average sleep duration in the study participants was 9 hours. The prevalence of sleep disorders was 7 % (PSQI, Pittsburgh Sleep Quality Index) and 10 % (ASBQ, Athlete Sleep Behavior Questionnaire) and among the youngest soccer players, this prevalence of violations was the lowest. Significant or moderate daytime sleepiness was found in 59 % of participants. The risk of serious disorders increased with age. Sleep disorders significantly affected injuries according to the results of the PSQI questionnaire and retrospective collection of information about injuries.Conclusion: the confirmed relationship between injuries and sleep disorders allows us to consider sleep quality improvement as an important component of injury and morbidity prevention among athletes of team sports.